Penerapan Pendekatan Kontekstual Dalam Menanamkan Nilai-Nilai Pendidikan Islam di Madrasah Ibtidaiyah - Sakirman, Sakirman (MODELING: Jurnal Program Studi PGMI, 2025)
Islamic education is an effort to improve the quality of individuals so that they remain consistent in practicing the teachings as Muslims. Currently, Islamic education is still far from the desired expectations, especially in terms of moral decline. This decline in morals has become a major problem that negatively impacts the values of Islamic education sources. Therefore, steps need to be taken to reduce these issues so that the values of Islamic education can provide mutual benefits. The contextual approach is presented as an effort to connect and strengthen the quality of Islamic education values. The research method used is a descriptive qualitative approach with a sample of students from Madrasah Ibtidaiyah data collection techniques were carried out through interviews and observations. Data analysis in this study includes data reduction, data presentation, and verification. Based on the discussion in this article, it can be concluded that the application of a contextual approach in Islamic education has a significant impact on students. This is due to the ability of contextual learning, which helps students connect the subject matter with its application in everyday life. A teacher needs to provide good education to students so that they can apply the values of monotheism and morality within themselves. Therefore, the ways to implement Islamic educational values with a contextual approach are by creating meaningful relationships, carrying out beneficial activities, organizing independent learning activities, collaborating, and guiding students to develop critical and creative thinking attitudes. Context: